2017
DOI: 10.1038/srep44998
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Polymeric Nanocapsules Prevent Cardiotoxicity of Anti-Trypanosomal Lychnopholide

Abstract: Chagas disease is a neglected parasitic disease caused by the protozoan Trypanosoma cruzi. New antitrypanosomal options are desirable to prevent complications, including a high rate of cardiomyopathy. Recently, a natural substance, lychnopholide, has shown therapeutic potential, especially when encapsulated in biodegradable polymeric nanocapsules. However, little is known regarding possible adverse effects of lychnopholide. Here we show that repeated-dose intravenous administration of free lychnopholide (2.0 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 61 publications
2
54
0
Order By: Relevance
“…However, in the plasma LYC may remain associated to NC for longer periods and be only partially released. This assumption is in agreement with the low cardiotoxicity of LYC in NC formulation 11 . In addition, the total LYC plasma levels do not necessarily represent the levels of free LYC available to exert pharmacological activity, considering that part of the LYC detected in the plasma can be associated to plasma proteins or remain encapsulated, as suggested by our release experiment.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, in the plasma LYC may remain associated to NC for longer periods and be only partially released. This assumption is in agreement with the low cardiotoxicity of LYC in NC formulation 11 . In addition, the total LYC plasma levels do not necessarily represent the levels of free LYC available to exert pharmacological activity, considering that part of the LYC detected in the plasma can be associated to plasma proteins or remain encapsulated, as suggested by our release experiment.…”
Section: Discussionsupporting
confidence: 86%
“…We developed and validated a simple bioanalytical method based on high performance liquid chromatography with ultraviolet detection (HPLC-UV) for the quantification of LYC in plasma samples, applicable to perform in vitro release kinetic studies and to compare the pharmacokinetics of LYC in mice after intravenous administration of the formulations. The data reported here provide the foundations to explain and correlate the recently reported enhanced efficacy 6 , 7 and reduced toxicity 11 of this new candidate in NC dosage form for the treatment of Chagas disease.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Sarcomere length (SL) shortening, an index of contraction, and intracellular Ca 2+ transients of left ventricular (LV) myocytes loaded with fluorescent ratiometric Ca 2+ indicator Indo-1AM (2 mM, Invitrogen Grand Island, NY, USA) were monitored with an IonOptix system (Milton, MA, USA) as described before (Branquinho, Roy, et al, 2017).…”
Section: Sarcomere Contraction and Measurements Of Intracellular Ca 2+mentioning
confidence: 99%
“…In addition, our group recently reported that nanostructured formulation is a strategy that can make a marked difference in vivo with improved efficacy and reduced toxicity of active compounds, including in the treatment of experimental Chagas disease by the oral route. [23][24][25] In this work, a RAV-SEDDS formulation for oral administration was developed and characterized. The safety of the formulation was evaluated in vivo in a 20-day treatment protocol in healthy mice and in T. cruzi-infected mice.…”
Section: Introductionmentioning
confidence: 99%